2019
DOI: 10.1016/j.actatropica.2018.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Growth-disrupting Murraya koenigii leaf extracts on Anopheles gambiae larvae and identification of associated candidate bioactive constituents

Abstract: Plant-based constituents have been proposed as eco-friendly alternatives to synthetic insecticides for control of mosquito vectors of malaria. In this study, we first screened the effects of methanolic leaf extracts of curry tree (Murraya koenigii) growing in tropical (Mombasa, Malindi) and semiarid (Kibwezi, and Makindu) ecological zones of Kenya on third instar An. gambiae s.s. larvae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…For instance, the limonoid azadirachtin isolated from Azadirachta indica (Meliaceae) is a well‐known example of a plant derived insecticide: further, numerous studies have reported larvicidal effect of plant extracts 9 or their constituents on diverse mosquito species 10,11 . Most of these larvicidal activities are attributed to specific classes of phytochemicals such as anthraquinones, 11 alkaloids, 12–14 limonoids 9,15,16 and terpenoids 17,18 …”
Section: Introductionmentioning
confidence: 99%
“…For instance, the limonoid azadirachtin isolated from Azadirachta indica (Meliaceae) is a well‐known example of a plant derived insecticide: further, numerous studies have reported larvicidal effect of plant extracts 9 or their constituents on diverse mosquito species 10,11 . Most of these larvicidal activities are attributed to specific classes of phytochemicals such as anthraquinones, 11 alkaloids, 12–14 limonoids 9,15,16 and terpenoids 17,18 …”
Section: Introductionmentioning
confidence: 99%